Unlikely Collaborations? Planning Experts from both Sides of the Iron Curtain and the Making of Abuja - Fenk, Anne-Katrin; Lee, Rachel; Motylińska, Monika (Comparativ, 2020)
As a so-called “playground of the Cold War”, post-colonial sub-Saharan Africa was contested territory in the ideological power game that dominated the second half of the twentieth century. However, despite the tension between eastern and western blocs, the non-aligned nations of the “South” also provided opportunities for unlikely collaborations. In the realm of urban planning, this can be observed in the development of new capital cities. Abuja, the new capital of Nigeria, serves as a potent example. While including a variety of voices (notably from the USA and UK), in this article we focus on the involvement of the GDR and particularly on the contribution of Heinz Schwarzbach. By providing analyses at both macro and micro scales, we hope to complicate existing Cold War planning histories. And even though the GDR appears as a minimal player, the fact that figures from the GDR took part in the Abuja project at all fundamentally questions the general narrative of the Cold War in Africa.